2008
DOI: 10.1200/jco.2008.16.3279
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Sorafenib in Advanced Thyroid Cancer

Abstract: A B S T R A C T PurposeGiven the molecular pathophysiology of thyroid cancer and the spectrum of kinases inhibited by sorafenib, including Raf kinase, vascular endothelial growth factor receptors, platelet-derived growth factor receptor, and RET tyrosine kinases, we conducted an open-label phase II trial to determine the efficacy of sorafenib in patients with advanced thyroid carcinoma. Patients and MethodsEligible patients with metastatic, iodine-refractory thyroid carcinoma received sorafenib 400 mg orally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
394
4
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(423 citation statements)
references
References 35 publications
16
394
4
9
Order By: Relevance
“…New smallmolecule protein-kinase inhibitors including axitinib [259], sorafenib [260,284,285], motesanib [262] and pazopanib [264] have shown promise in clinical trials on thyroid cancer. PLX4032 (also known as vemurafenib), a BRAF-V600E-specific inhibitor, has been recently approved by the FDA for the treatment of BRAFV600E-positive melanoma [286].…”
Section: Discussionmentioning
confidence: 99%
“…New smallmolecule protein-kinase inhibitors including axitinib [259], sorafenib [260,284,285], motesanib [262] and pazopanib [264] have shown promise in clinical trials on thyroid cancer. PLX4032 (also known as vemurafenib), a BRAF-V600E-specific inhibitor, has been recently approved by the FDA for the treatment of BRAFV600E-positive melanoma [286].…”
Section: Discussionmentioning
confidence: 99%
“…Our study results might also be pertinent to therapeutic decision-making. There is growing evidence that BRAF mutation-targeted therapy (sorafenib) is effective in metastatic or advanced thyroid cancer [26][27][28]. There was also a report that in iodine-refractory differentiated thyroid cancer, an early 18 F-FDG PET response was useful for identifying sorafenib non-responders, although no BRAF mutation analysis was performed in those patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Using prolonged SD measures as reported by other investigators, we observed 36% of patients with SD lasting over 24 weeks which compares favorably with the SD proportions with axitinib (38% over 16 weeks), sorafenib (53% from 14–89+ weeks), and motesanib (35% over 24 weeks; refs. 2729). Similar to the case for response rates, patients treated with selumetinib showed PFS rates that were shorter than for the 3 comparator studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only 16% of patients discontinued selumetinib therapy due to adverse events. Reported objective response rates have been greater in recent studies in advanced thyroid cancer of agents (axitinib, motesanib, sorafenib, and sunitinib) that target the vascular endothelial growth factor receptor (VEGFR) compared with agents such as selumetinib and gefitinib that do not target the VEGFR (2729, 31, 32). This observation suggests that angiogenesis may be more important in progression of disease than signaling pathways known to be activated in the tumor such as RAS/RAF/MAPK activation.…”
Section: Discussionmentioning
confidence: 99%